2011
DOI: 10.1007/s10397-011-0706-4
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and long-term efficacy of hysteroscopic myomectomy for myomas with intramural development by the use of non-electrical “cold” loops

Abstract: This study aimed to assess the feasibility and the short-and long-term efficacy of hysteroscopic myomectomy for submucous myomas with intramural development [grade 1 (G1) and grade 2 (G2)] by using non-electrical "cold" loops and to verify the role of preoperative variables on surgical outcomes. Symptomatic (bleeding and infertility) premenopausal patients with the diagnosis of submucous myoma at transvaginal sonography, and with G1 and G2 grading at sonohysterography, were included in this prospective study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
(28 reference statements)
2
12
0
Order By: Relevance
“…Previous studies revealed that hysteroscopic excision of large myomas and myomas with intramural extension are associated with increased risks of uterine perforation, cervical laceration, and intravasation of excessive amounts of distension media. The incidence of major complications in previous studies ranged between 2.75% and 9.01% [16,18].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies revealed that hysteroscopic excision of large myomas and myomas with intramural extension are associated with increased risks of uterine perforation, cervical laceration, and intravasation of excessive amounts of distension media. The incidence of major complications in previous studies ranged between 2.75% and 9.01% [16,18].…”
Section: Discussionmentioning
confidence: 98%
“…I and type II submucous myomas revealed that the rates of 1-step complete removal for type I and type II submucous myomas were 92% and 85%, respectively [16]. In a prospective study including 59 patients with submucous myomas with intramural development, Bettocchi et al [10] used a bipolar Versapoint twizzle electrode or scissors (Gynecare; Ethicon Inc., Somerville, NJ) to incise the mucosa covering the myoma at the level of its reflection on the uterus.…”
Section: Discussionmentioning
confidence: 98%
“…None of the good quality series falls among the ones in which estimating the rare event has been needed. In the study of Leone et al [54], the main myoma diameter was reported as median. Hallez et al [44] provided intervals for diameters of myoma.…”
Section: Discussionmentioning
confidence: 99%
“…This classification includes intracavitary fibroids only; cervical fibroids are not contemplated. Hysteroscopic myomectomy may be performed by different techniques: direct mobilization, slicing, or both [6,7]. It can be used with U or L resectoscope handle, with or without energy, either monopolar or bipolar.…”
Section: Introductionmentioning
confidence: 99%